Odpowiedź :
Odpowiedź:
5/(x + 4) - 2/(x - 4) + 40/(x² - 16)
założenie:
x²- 16 ≠ 0
(x + 4)(x - 4) ≠ 0
x + 4 ≠ 0 ∧ x - 4 ≠ 0
x ≠ - 4 ∧ x ≠ 4
D: x ∈ R \ {- 4 , 4 }
Ponieważ x² - 16 = (x + 4)(x - 4) , więc :
[5(x - 4) - 2(x + 4) + 40]/(x² - 16) = (5x - 20 - 2x - 8 + 40)/(x² - 16) =
= (3x + 12)/(x² - 16) = 3(x+ 4)/[(x + 4)(x - 4)] = 3/(x-4)
Szczegółowe wyjaśnienie:
zał: [tex]x+4\neq 0[/tex] [tex]i[/tex] [tex]x-4\neq 0[/tex]
[tex]x\neq -4[/tex] [tex]x\neq 4[/tex]
[sprowadzamy wyrażenie do wspólnego mianownika: [tex](x-4)(x+4)[/tex]]
[tex]\frac{5}{x+4} -\frac{2}{x-4} +\frac{40}{x^{2} -16} =[/tex] [tex]=\frac{5}{x+4} -\frac{2}{x-4} +\frac{40}{(x -4)(x+4)} =[/tex]
[tex]=\frac{5(x-4)}{(x+4)(x-4)} -\frac{2(x+4)}{(x-4)(x+4)} +\frac{40}{(x-4)(x+4)} =[/tex]
[tex]=\frac{5(x-4)-2(x+4)+40}{(x-4)(x+4)}=\frac{5x-20-2x-8+40}{(x-4)(x+4)} =[/tex]
[tex]=\frac{3x + 12}{(x-4)(x+4)} =\frac{3(x+4)}{(x-4)(x+4)} =[/tex] ←skracamy (x+4)
[tex]=\frac{3}{x-4}[/tex]
Korzystamy ze wzoru skróconego mnożenia: [tex]a^{2} -b^{2} =(a-b)(a+b)[/tex]